The effect of oil sands process-affected water and model naphthenic acids on photosynthesis and growth in Emiliania huxleyi and Chlorella vulgaris. (February 2016) - Beddow, Jessica; Johnson, Richard J.; Lawson, Tracy; Breckels, Mark N.; Webster, Richard J.; Smith, Ben E.; Rowland, Steven J.; Whitby, Corinne
Abstract: Naphthenic acids (NAs) are among the most toxic organic pollutants present in oil sands process waters (OSPW) and enter marine and freshwater environments through natural and anthropogenic sources. We investigated the effects of the acid extractable organic (AEO) fraction of OSPW and individual surrogate NAs, on maximum photosynthetic efficiency of photosystem II (PSII) ( F V / F M ) and cell growth in Emiliania huxleyi and Chlorella vulgaris as representative marine and freshwater phytoplankton. Whilst F V / F M in E. huxleyi and C. vulgaris was not inhibited by AEO, exposure to two surrogate NAs: (4′- n -butylphenyl)-4-butanoic acid ( n -BPBA) and (4′- tert -butylphenyl)-4-butanoic acid ( tert -BPBA), caused complete inhibition of F V / F M in E. huxleyi (≥10 mg L −1 n -BPBA; ≥50 mg L −1 tert -BPBA) but not in C. vulgaris . Growth rates and cell abundances in E. huxleyi were also reduced when exposed to ≥10 mg L −1 n - and tert -BPBA; however, higher concentrations of n - and tert -BPBA (100 mg L −1 ) were required to reduce cell growth in C. vulgaris . AEO at ≥10 mg L −1 stimulated E. huxleyi growth rate (p ≤ 0.002), yet had no apparent effect on C. vulgaris . In conclusion, E. huxleyi was generally more sensitive to NAs than C. vulgaris . This report provides a better understanding of the physiological responses of phytoplankton to NAs which will enable improved monitoring of NA pollution in aquatic ecosystems in the future. Highlights: Emiliania huxleyi was generally more sensitive than Chlorella vulgaris to surrogate NAs. Surrogate NAs at 10–50 mg L −1 inhibited F V / F M and growth in E. huxleyi but not C. vulgaris . F V / F M in C. vulgaris and E. huxleyi was not inhibited by the AEO fraction of OSPW. The AEO fraction of OSPW at ≥10 mg L −1 stimulated cell growth in E. huxleyi .